Energy Range of Electron Rolling Pin Distribution Behind Dipolarization Front. Issue 5 (14th March 2019) - Zhao, M. J.; Fu, H. S.; Liu, C. M.; Chen, Z. Z.; Xu, Y.; Giles, B. L.; Burch, J. L.
Abstract: The electron rolling pin distribution, showing electron pitch angles primarily at 0°, 90°, and 180°, has recently been observed behind dipolarization fronts (DFs) and explained using an analytical model. However, the energy range of such distribution has been unknown so far, owing to the low‐resolution data in previous spacecraft missions. Here using the high‐resolution measurements of Magnetospheric Multiscale, we reveal the energy range of electron rolling pin distribution behind DFs for the first time. We find that such distribution appears only above 1.7 keV, falling well into the suprathermal energy range. Below 1.7 keV, electrons exhibit a Maxwell distribution, while above 1.7 keV, they exhibit a power law distribution. In addition, such distribution appears primarily in the growing phase of the flow and disappears quickly in the decaying phase. During the formation of the rolling pin distribution, electrons are gyrotropic. These findings have greatly improved our knowledge of electron dynamics around DFs. Plain Language Summary: Examining the electron pitch angle distribution can help us understand the electron dynamics behind dipolarization fronts (DFs). Up to now, the energy range of electron rolling pin distribution, which shows electron pitch angles primarily at 0°, 90°, and 180°, has been unknown, owing to the low‐resolution data in previous spacecraft missions. Here using the high‐resolution Magnetospheric Multiscale measurements, we reveal the energy range of electron rolling pin distribution behind DFs for the first time. Our findings can significantly improve the knowledge of electron dynamics around DFs. Key Points: Rolling pin distribution appears only above 1.7 keV, falling well into suprathermal energy range Below 1.7 keV, electrons have Maxwell distribution; above 1.7 keV, they have power law distribution During the formation of the rolling pin distribution, electrons are gyrotropic